AN ANALYTICAL STUDY OF PRAJASTHAPAN MAHAKASHAYA ON VANDHYATWA W. S. R. TO FEMALE INFERTILITY - Prachi, Singh; Yadav, R. B.; Shakya, Sadhna (International Journal of Ayurveda and Pharma Research, 2015)
In Charaka samhita, among the fifty important decotives, Prajasthapan mahakashaya (fertility promoters) was introduced according its Doshaj prabhav (specific action) of the drugs and promotes strength and conceiving by removing Doshas to female reproductive system. These drugs are also having Rasayana properties, which improve the quality of all body elements. These herbs can be used all together or individually or in permutation combinations of each other on the patient's condition. In short, Prajasthapan mahakashaya can be used in all conditions involving obstruction in the path of conception and help in fixing or lead to excellence in progeny. Female Vandhyatwa (Infertility) may cause twenty Yoni vyapad (gynaecological disorders), infections, weakness, psycological factors like anxiety, depression etc., may leads disturbance in the Ritu (fertile period), Ambu (nourishment for developing the zygote), Beeja (activated ovum), Kshetra (Physiological maturity and healthy organs of reproductive system). The objective of the present study is an analytical study of Prajasthapak mahakashay on Vandhyatwa with special reference to female infertility and to analyse all ten drugs of Prajasthapan Mahakashaya to collect the information on latest studies on above mentioned factors.